IMPLEMENTATION OF RCM IN MAINTENANCE STRATEGY OF FO SYSTEM, LO SYSTEM, AND COOLING SYSTEM MAIN ENGINE - Yudo, Hartono; Nizar, Vania Early; Hadi, Eko Sasmito; Mulyatno, Imam Pudjo (IJMEA International Journal of Marine Engineering and Applications, 2026)
The performance of a ship’s main engine largely depends on the reliability of its three primary subsystems: fuel, lubricating, and cooling. These systems must operate optimally to ensure efficiency and safety under varying operational conditions. This study evaluates the reliability of the KM. Lawit main engine subsystems using the Reliability Centered Maintenance (RCM) approach. Four analytical methods were applied: Failure Mode and Effect Analysis (FMEA) to identify critical components, Fault Tree Analysis (FTA) to trace root causes of failures, Reliability Block Diagram (RBD) to model interrelationships, and Monte Carlo simulation to estimate system reliability probabilistically. The analysis was based on operational and maintenance data from 2023–2024. FMEA identified the duplex filter in the fuel system (RPN = 288), the lubricating oil filter (RPN = 280), and the expansion tank in the cooling system (RPN = 140) as the most critical components requiring priority maintenance. Monte Carlo simulation over a 3,250-hour period showed the cooling system achieved the highest reliability, with a Mean Time to Failure (MTTF) of 1,022.21 hours and a Mean Time Between Failures (MTBF) of 7,587.47 hours. Across all systems, availability levels exceeded 99%, indicating strong reliability and minimal risk of operational failure. These findings highlight the effectiveness of integrating FMEA, FTA, RBD, and Monte Carlo simulation within the RCM framework. The results emphasize the need for preventive maintenance strategies to sustain the long-term operational stability and safety of the main engine